PEMBUATAN PERANGKAT LUNAK CAM UNTUK MESIN CNC FREIS 3 SUMBU PADA AutoCAD - Sigit Yoewono Martowibowo; Wildan Rojuli Daa'i (Mesin, 2004)
This study is aimed to produce CAM software run under AutoCAD 2000 or latest version using Visual Basic for Application (VBA) program. Machining processes are carried out using endmill cutter at X-Y plane. Input of this software is 3-D drawings of the model. The output of this software are G-Code of cutting tool path. The software also provides fasilities to approach spline and ellips with connected lines but still considering geometric tolerances of line profile.